(untitled) (Fiep Bulletin - online, 2011)
The theme â€œcompetitionâ€ in the childhood and in the adolescence is polemic being the goal of constant discussion among the area studies. The big questioning is if the competitive sports provide real benefits in the physiological, psychological and social aspects to the young athletes. The coach has a predominant role in the perception in what the athlete does of the competition and of the way how the athlete is going to face it, his or her leadership style, this may interfere in the biopsychosocial aspects. The way how the coaches are going to intervene during the interval and/or during a match has a relevant impact in the athlete production. This work has like objective to identify the basketball coach leadership style participant of Children School Olympics under athletes perception. Four coaches and forty-eight athletes of children category of male and female basketball team take part of this study. It was used a structural questionnaire of closed questions to the teacher/coach characterization and an interview with a generation question to verify the athletes perception and the teacherâ€™s behavior. The date analyses to the teacher characterization was conducted with the descriptive statistics resources and to verify the athletes perception it was used Content Analysis a qualitative approach. We note in this study, the athletes of team I and II in which the coaches were characterized the most experienced in the competition and the modal, they had a positive perception with high level of approval to the coach leadership style in all aspects: personal, professional, instruction and feedback. While the I and II teams coaches, with less experienced in competitions and in basketball modal, had their leadership style evaluated like a positive aspect and negative in the professional, instruction and feedback aspects.